Reproductive Tract Infections and Treatment Seeking Behavior among Married Adolescent Women 15-19 Years in India - Ranjan Kumar Prusty, MPS; Sayeed Unisa, PhD (Global Health and Education Projects, Inc., 2013)
Background: India is home to the highest number of adolescents in the world. Adolescents in India suffer from lack of knowledge and empowerment to make informed sexual and reproductive health decisions. This paper analyses the prevalence of reproductive tract infections and sexually transmitted infections (RTI/STI) and treatment seeking behavior among married adolescent women in India aged 15-19 years. Methods: Data from the District Level Household Survey (DLHS, 2007-08) of India were used. The prevalence of RTIs symptoms and treatment seeking behavior among women by different socio-demographic characteristics was analyzed. Factor analysis was utilized to create an index using information about 11 symptoms of RTI/STI collected in the survey. Linear and binary logistic regressions were used to know the association between infections and treatment seeking behavior with socio-demographic factors. Results: About 15 percent of adolescent women reported having any symptoms of RTI/STI. The main symptoms reported were low backache, pain in the lower abdomen, pain during intercourse and itching or irritation around the vulvar region. Factor analysis showed the concentration of diseases in three clusters - infection in around the vulva, other reproductive infection and abnormal discharge; and intercourse related problems. Major predictors of both symptoms of reproductive infections and treatment seeking behavior from multivariate analysis are age, education, wealth, region and awareness about RTI/STI. Conclusion and Public Health Implications: Knowledge and treatment seeking behavior is poor among adolescent women in India. There is need for programmatic and policy emphasis on increasing knowledge and awareness through family life education including in educational curriculum at school level.